Cultivating Gender Sensitive Culture In The Malaysian Media Industry: A Critique And An Alternative. - Azmawati, Dr. Azman Azwan (2006)
Media's treatment on gender issues has always been a vital concern of many, especially strong advocates of human rights principles, who view detrimental treatment of women as one of the major impediments in achieving gender equality.